Islamic Banking Risk Assessment Process: A Case Study from Indonesia - Sitasari, Ita (Journal Of Middle East and Islamic Studies, 2021)
Indonesian Islamic banks are required have minimum capital in relation to bank’s risk profile rating that comes from the comprehensive risk assessment process. This is a qualitative study to observe how Islamic banks in Indonesia respond to the regulation, with the focus observation on the material risk identification process, risk indicators and determination of risk level. Based on discussion with some risk officers of Islamic banks indicates that the banks do not have specific process to identify material risks. They make assessment on risk types that have been defined by regulator. They also do not develop additional Islamic risk indicators to describe the unique risks of Islamic transactions. They just follow the risk indicators that have been defined by regulator. To determine the rating of each material risk, they defined some scales and threshold derived from the bank’s risk appetite and tolerance. From the observation of annual reports, it was found that not all banks disclose their risk profile rating. The number of respondents were limited compared to the number of all Islamic banks therefore the result of discussion might not represent the population. Future research is required to develop methodology for a comprehensive risk assessment for Islamic banks as a prerequisite for the implementation of ICAAP